Total Dissolved Solids on Turmeric Emulsion (Curcuma longa L.) Affected by Iota and Kappa Carrageenan - Lusida Mulia Arganis; Heni Rizqiati; Anang Mohamad Legowo; Yoyok Budi Pramono; Ahmad Ni'matullah Al-Baarri (Journal of Applied Food Technology, 2018)
The quality of emulsion such as total dissolved solids, may be determined by type of emulsifier. Carrageenan is a polysaccharide from red seaweed (Rhodophyceae) and it is well known as emulsifier, however the application of carrageenan has not widely used in traditional beverage in Java Island, Indonesia. Therefore, the purpose of this research was to determine the effect of carrageenan in turmeric emulsion on its total dissolved solids. Distribution of total dissolved solids was tested using total dissolved solid-meter. Iota and kappa carrageenan were used. As a result, carrageenan might increase total dissolved solid at 58±3.4% and iota had reached higher total dissolved solid than kappa. As conclusion, total dissolved solid might be elevated by the addition of carrageenan.